2001
DOI: 10.1063/1.1346685
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory studies of the adsorption of ethylene and oxygen on Pt(111) and Pt3Sn(111)

Abstract: Density functional theory, employing periodic slab calculations, was used to investigate the interactions of ethylene and oxygen with Pt͑111͒ and Pt 3 Sn(111). The predicted energetics and structures of adsorbed species on Pt͑111͒ are in good agreement with experimental data. The binding energies of -bonded ethylene, di--bonded ethylene, and ethylidyne species are weaker on Pt 3 Sn(111) than on Pt͑111͒ by 21, 31, and 50 kJ/mol, respectively. Hence, the electronic effect of Sn on the adsorption of ethylene depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
60
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 78 publications
16
60
0
1
Order By: Relevance
“…Dehydrogenation is a structure insensitive reaction requiring a single active atom [46,47] while hydrogenolysis is a structure sensitive reaction requiring an ensemble of active atoms [47]. It has been shown that Pt 3-fold hollow sites present in large Pt ensembles are responsible for the formation of strongly adsorbed alkylidyne species which are precursors of hydrogenolysis and coke forming reactions [48][49][50][51]. The formation of Pt 3 In reduces the number of Pt 3-fold hollow sites and it has been shown that the formation of ethylidyne is suppressed on Pt 3 Sn alloys with equivalent structures to the Pt 3 In phase in Pt-In(0.7) [48,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrogenation is a structure insensitive reaction requiring a single active atom [46,47] while hydrogenolysis is a structure sensitive reaction requiring an ensemble of active atoms [47]. It has been shown that Pt 3-fold hollow sites present in large Pt ensembles are responsible for the formation of strongly adsorbed alkylidyne species which are precursors of hydrogenolysis and coke forming reactions [48][49][50][51]. The formation of Pt 3 In reduces the number of Pt 3-fold hollow sites and it has been shown that the formation of ethylidyne is suppressed on Pt 3 Sn alloys with equivalent structures to the Pt 3 In phase in Pt-In(0.7) [48,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…23 The 2 × 2 two-layer unit cell, containing 6 Pt atoms and 2 Sn atoms, was repeated periodically, with four equivalent layers of vacuum between any two successive metal slabs. Total energy calculations were performed using DACAPO.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, these improvements have been attributed to both geometric as well as electronic effects. [13][14][15][16][17][18][19] Tin atoms on the surface of Pt clusters are known to frustrate the formation of larger active ensembles, which suppresses undesired C-C bond cleavage processes that lead to coke formation and deactivation. 9,[20][21][22][23][24][25][26][27] Careful comparison of catalyst activities at varying residence times reveals an intrinsically higher activity of the alloy compared to pure Pt clusters, 12 indicating the presence of beneficial electronic effects as suggested by theoretical work on metal surfaces.…”
Section: Introductionmentioning
confidence: 99%